The effects of graphene oxide nanoparticle additive stably dispersed in dairy scum oil biodiesel-diesel fuel blend on CI engine: performance, emission and combustion characteristics - Soudagar, Manzoore Elahi M.; Nik-Ghazali, Nik Nazri; Kalam, Md. Abul; Badruddin, Irfan Anjum; Banapurmath, N.R.; Yunus Khan, T.M.; Bashir, Muhammad Nasir; Akram, Naveed; Farade, Rijavan; Afzal, Asif (Elsevier, 2019)
In the present investigation, the effects of graphene oxide nanoparticles on performance and emissions of a CI engine fueled with dairy scum oil biodiesel was studied. Nanofuel blend was prepared by dispersing graphene oxide in varying quantities in dairy scum oil methyl ester (DSOME)-diesel blend. Sodium dodecyl sulfate (SDS) was used as a surfactant for a steady dispersion of graphene oxide nanoparticles in the fuel blends. The dispersion and homogeneity were characterized by ultraviolet–visible spectrometry. An ideal graphene-to-surfactant ratio was defined, highest absolute value UV-absorbency was seen for a mass fraction of 1:4. The concentration of surfactant above or below this ratio resulted in reduction in the stability of dispersion. Graphene oxide nanoparticles were amalgamated with dairy scum oil biodiesel at proportions of 20, 40 and 60 parts per million using ultrasonication technique. Experiments were performed at a constant speed and varying the brake power and load condtions. The results were notable enhancements in the performance and emissions characteristics, the brake thermal efficiency improved by 11.56%, a reduction in brake specific fuel consumption by 8.34%, unburnt hydrocarbon by 21.68%, smoke by 24.88%, carbon monoxide by 38.662% for the nanofuel blend DSOME2040 and oxides of nitrogen emission by 5.62% for fuel DSOME(B20). Similarly, the addition of graphene nanoparticles in DSOME fuel blends resulted in significant reduction in the combustion duration, ignition delay period, improvement in the peak pressure and heat release rate at maximum load condition. Finally, it is concluded that nano-graphene oxide nanoparticles can be introduced as a suitable substitute fuel additive for dairy scum oil biodiesel blends to enhance the overall engine performance and emissions characteristics. © 2019 Elsevier Ltd